Elaboração de filme ativo e biodegradável a base de queratina e hidrolisado proteico extraídos da pena de frango caipira - Santos, Miriane Moreira Fernandes (2023)
The Northeast of Brazil stands out in the free-range chicken chain and has the largest production slaughterhouses. The purpose of slaughtering chickens is mainly to sell the meat, ignoring other parts such as feathers, head, skin, viscera and blood. The feather is one of the most produced by-products and has a rich composition with around 90% protein, especially keratin. Despite this, most feathers are still underutilized or even discarded inappropriately, contributing to the worsening of environmental pollution. Thus, the objective was to make use of free-range chicken feathers to make biodegradable and active films from keratin and protein hydrolysate of the by-product. Keratin was obtained through a chemical method, using 3.5 M urea and 0.1 M sodium sulfite. The protein hydrolysate was obtained through the action of Flavourzyme and Alcalase enzymes (5% for 240 minutes), in addition to an alkaline microwave pre-treatment (1400 W/10 minutes in 0.5 M NaOH). The hydrolysates were submitted to the evaluation of technological and functional properties (oil retention capacity, emulsifying capacity, thermal stability and antioxidant activity). The films were prepared using the casting technique with corn starch and glycerol added as a plasticizer and then characterized. Free-range chicken feathers showed high protein concentration and low lipid content, both on a dry basis (85.92±1.92 g/100g and 1.04±0.09 g/100g, respectively). The application of alkaline pre-treatment in microwaves promoted greater feather solubilization, which varied between 89.69 – 91.73%. In addition, it was also responsible for promoting hydrolysates with a higher soluble protein content (68.72 – 72.78 mg/mL). The type of enzyme used to obtain the hydrolysates (Alcalase or Flavourzyme) did not influence the oil retention capacity, emulsifying capacity and emulsion stability. However, for the antioxidant capacity, the application of the enzyme Flavourzyme contributed to a better performance, since the hydrolysates obtained through its action showed higher values against DPPH radicals (257.22 μmol Eq Trolox/mL) and ABTS (3362.80 μmol Eq Trolox/mL), as well as the ability to reduce the iron ion - FRAP (340.44 μmol Eq Ferrous Sulfate/mL). For films based on keratin from free-range chicken feathers, the influence of protein hydrolysate concentrations (0%; 1.5%; 3.0%; 6.0%) on different properties was observed. Solubility (60.46%), water vapor permeability (0.96x10-3 gH2O mm/m²h mmHg) and antioxidant potential (DPPH: 371.97±9.19; ABTS: 15.37±1.94) showed better results for films produced with 6% protein hydrolysate. Despite this, all films showed a high percentage of degradability after 15 days (89.85 – 97.37%), which indicates that this can be a promising biomaterial for packaging production. Therefore, it is possible to conclude that free-range chicken feathers have the potential to obtain keratin and protein hydrolysates with technological and functional properties capable of providing active and biodegradable films, becoming an alternative to add value and reduce the disposal of these by-products. in the environment. In addition, the application of microwaves in conjunction with hydrolysis using the Flavourzyme enzyme proved to be an efficient technique for the production of peptides with antioxidant potential.